Cerebral Small Vessel Disease. Issue 12 (December 2018) - Li, Qian; Yang, Yang; Reis, Cesar; Tao, Tao; Li, Wanwei; Li, Xiaogang; Zhang, John H.
Cerebral small vessel disease (CSVD) is composed of several diseases affecting the small arteries, arterioles, venules, and capillaries of the brain, and refers to several pathological processes and etiologies. Neuroimaging features of CSVD include recent small subcortical infarcts, lacunes, white matter hyperintensities, perivascular spaces, microbleeds, and brain atrophy. The main clinical manifestations of CSVD include stroke, cognitive decline, dementia, psychiatric disorders, abnormal gait, and urinary incontinence. Currently, there are no specific preventive or therapeutic measures to improve this condition. In this review, we will discuss the pathophysiology, clinical aspects, neuroimaging, progress of research to treat and prevent CSVD and current treatment of this disease.